1/6(y+42)+15=-3

Simple and best practice solution for 1/6(y+42)+15=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6(y+42)+15=-3 equation:



1/6(y+42)+15=-3
We move all terms to the left:
1/6(y+42)+15-(-3)=0
Domain of the equation: 6(y+42)!=0
y∈R
We add all the numbers together, and all the variables
1/6(y+42)+18=0
We multiply all the terms by the denominator
18*6(y+42)+1=0
Wy multiply elements
108y(y+1=0

See similar equations:

| -11+10x+11-x-2x-33=100 | | 14-5=-8y+7y | | -2m+5=3m-10 | | 6(-4+5x)=-24+2x | | 4x=3x-5-2x | | 5x-5(0)=5 | | 13+5x=21-3x | | 5x+9+5x-30-7x=30 | | y/5+6=-19 | | 5=2m-30+3m | | 4c=-15+7c | | 8+0.75x=6=1.25x | | 6(6x+6)-4=6x | | 4-3x=30-5x | | 1+2n=-2+2n | | 3+7x=+23 | | (3m+2)(m+1)=7-7m | | 2b-6=6+4b | | -5​(n-3​)=9-4n | | 12x+25=3x+10 | | P(x)=11.5x-0.1x-150 | | P(x)=11.5x-0.1-150 | | (18-2x)(29-2x)=152 | | 2(5x-3)-(2x-4)=-(6x=1) | | 5x-3(x+2)=-7+2(x-3) | | x+3(-19/11)=-6 | | 1/2x+8-6=4 | | 11x+15=5x-19 | | -(8+3x)+5=2x+5 | | .30x+140=x | | 3(x+2)+9=42 | | -10k−6=9−7k−8k |

Equations solver categories